Relationship between preoperative plasma fibrinogen and prognosis in patients with non-metastatic gastric cancer: a systematic review and meta-analysis - Lei, Yan-Rong; Lv, Lu; Lu, Chi (Frontiers in Oncology, 2025)
BackgroundPreoperative plasma fibrinogen (Fib) is a potential prognostic marker for various cancers, including gastric cancer. This systematic review and meta-analysis aimed to investigate the relationship between preoperative fibrinogen levels and prognosis in patients with non-metastatic gastric cancer patients.MethodsThis meta-analysis was conducted in accordance with the PRISMA guidelines. A comprehensive literature search of PubMed, Embase, Web of Science, and Cochrane Library was performed up to May 26, 2025, without language or date restrictions. Eligible studies reported multivariate-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for overall survival (OS) and recurrence-free survival (RFS) in relation to preoperative fibrinogen levels. Subgroup and sensitivity analyses were performed, and study quality was assessed using the Newcastle-Ottawa Scale (NOS).ResultsA total of 8 retrospective studies involving 4,281 patients were included. Pooled analysis revealed that elevated fibrinogen levels were significantly associated with poorer OS (HR = 1.56, 95% CI: 1.20–1.93, P < 0.001; I² = 57.0%) and RFS (HR = 2.08, 95% CI: 1.33–2.82, P < 0.001; I² = 0%). Subgroup analyses confirmed consistent associations across age, sex, tumor stage, geographic region, and fibrinogen cut-off values. No significant publication bias was detected.ConclusionsElevated preoperative fibrinogen levels are significantly associated with worse overall and recurrence-free survival in patients with non-metastatic gastric cancer, indicating its potential utility as a prognostic biomarker. Given the limited data on RFS, further large-scale prospective studies are needed to validate these findings and support its integration into individualized risk stratification models.